Metode Profile Matching Sistem Pendukung Keputusan Untuk Menentukan Orang Dalam Gangguan Jiwa - Rahayu, Tri; Wirawan, Rio; Krisnanik, Erly (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
The Profile Matching method is a technique in decision support systems that is used to analyze the conformity of criteria with predetermined standards. In the context of determining mental disorder status, this method plays a role in identifying individuals based on certain mental health criteria. The process involves comparing an individual's profile with a standard profile that describes the characteristics of mental disorders. The criteria analyzed include aspects of the indicators, namely; Emotional, Physical, Behavioral and Psychological relevant to mental health. This method is able to provide objective recommendations because it uses weight-based calculations for each criterion. This Profile Matching-based decision support system can help health workers and decision makers at the village level to identify and group individuals with mental disorders, so that appropriate interventions can be determined. With this system, the process of evaluating people's mental health conditions can be carried out more accurately and efficiently. This method is one method of determining the indication that a person is classified as an ODGJ with the indicators, namely; Emotional, Physical, Behavioral and Psychological. Based on research results from 5 patients who were tested using the Profile Matching method, the following results are in the highest order; Patient F had the highest score, namely 3.7, patient R, namely 3.4, patient C, namely 3.3, patient S, namely 3.2 and the smallest was patient A, namely 3.0. It is hoped that it can increase early detection of mental disorders, as well as speed up follow-up treatment or referral to further mental health services.